2020
DOI: 10.1113/jp279195
|View full text |Cite
|
Sign up to set email alerts
|

Step time asymmetry but not step length asymmetry is adapted to optimize energy cost of split‐belt treadmill walking

Abstract: Key points The relationship between spatiotemporal gait asymmetry and walking energetics is currently under debate. The split‐belt treadmill paradigm has been used to study adaptation of spatiotemporal gait parameters in relation to energetics, but it remains unclear why people reduce asymmetry in step lengths, but prefer asymmetry in step times. In this study we characterized the effects of step time asymmetry and step length asymmetry on energy cost during steady‐state walking on a split‐belt treadmill at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 43 publications
8
24
0
Order By: Relevance
“…In either case, the temporal component was free to express the adapted asymmetry, independent of the spatial component, during the transfer condition. These results are consistent with previous findings that spatial and temporal control of walking gait are dissociable [4][5][6]8,20]. A recent study demonstrated that manipulation of spatial control during split-belt adaptation had no effect on temporal after-effects, but manipulation of temporal adaptation influenced the spatial aftereffects [8].…”
Section: Transfer Of Temporal But Not Spatial Adaptation To Non-motorsupporting
confidence: 92%
“…In either case, the temporal component was free to express the adapted asymmetry, independent of the spatial component, during the transfer condition. These results are consistent with previous findings that spatial and temporal control of walking gait are dissociable [4][5][6]8,20]. A recent study demonstrated that manipulation of spatial control during split-belt adaptation had no effect on temporal after-effects, but manipulation of temporal adaptation influenced the spatial aftereffects [8].…”
Section: Transfer Of Temporal But Not Spatial Adaptation To Non-motorsupporting
confidence: 92%
“…Also, Figure 6 shows how the energy cost landscape has greater curvature along step time asymmetry rather than the step length asymmetry, again implying faster convergence for the energy optimizing gradient descent in the step time direction than in the step length direction. One recent study 38 with a shorter adaptation timescale observed that in that short timescale, split belt walking converged to the energy optimal step time but not the energy optimal step length. This may simply be because, as our model suggests, step time asymmetry may converge faster than step length asymmetry due to the aforementioned reasons.…”
Section: Resultsmentioning
confidence: 99%
“…This can be explained by the angle between the longitudinal axis of the foot and the walking direction; negative values indicate an inward rotation and positive values indicate an outward rotation. Healthy human walking is symmetrical and economical; however, the walking of people who received AA is often asymmetrical and requires more energy [ 18 ].…”
Section: Discussionmentioning
confidence: 99%